Starting a Home and Mobile HIV Testing Service in a Rural Area of South Africa - Maheswaran, Hendramoorthy (J Acquir Immune Defic Syndr, 2012)
OBJECTIVE: To compare users of a home and mobile HIV counseling and testing service implemented in rural KwaZulu-Natal, South Africa. METHODS: Communities of similar population size and density were allocated HIV counseling and testing provision be either home or mobile services. Uptake of services was compared, including results from a brief questionnaire. RESULTS: Majority of individuals proceeded to test. Mobile services reported a higher proportion of clients who were male (41% vs. 31%; P < 0.001), younger than 25 years (53% vs. 28%; P < 0.001), single (66% vs. 40%; P < 0.001), and never previously tested (62% vs. 56%; P = 0.003). Home services reported a higher proportion of clients older than of 35 years (56% vs. 35%; P < 0.001) and married/partner (43% vs. 30%; P < 0.001). HIV prevalence amongst clients of the 2 services was comparable, with both services testing more clients daily than the local primary health care clinics, but similar to the local hospital. CONCLUSIONS: The numbers tested, different populations reached, and high detection rates suggest both modalities have an important role to play, especially in rural communities where cost of transport may be a deterrent.